IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DALAM PEMBELAJARAN MATEMATIKA PADA SISWA KELAS VII MTSN 1 KOTABARU - Andi Karlina; Faisal Batennie (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
This research is an experimental research that involves one group that aims to determine the application of Numbered Heads Together (NHT) type cooperative learning model for mathematics learning in class VII A MTsN. 1 Kotabaru which is viewed from (1) student learning completeness, (2) student activity in the learning process, (3) teacher's ability to manage learning, and (4) student's response to learning. The subjects of this study were students of class VII A MtsN 1 Kotabaru in the Odd Semester, 2017/2018 Academic Year, as many as 24 students consisting of 14 male students, 10 female students. Data retrieval is done using tests of mathematics learning outcomes, observation of student and teacher activities, and questionnaires to determine students' responses to learning. The results obtained are as follows: (1) student learning achievement that is from 24 students as research subjects there are 20 (83.33%) who complete and 4 (16.67%) who do not complete individually, (2) student activities related to learning activities from all aspects observed, most have been implemented, (3) Teacher activity in mathematics learning through Numbered Heads Together (NHT) cooperative learning model is generally implemented entirely, (4) student response to cooperative learning model type Numbered Heads Togethetr (NHT) in mathematics learning generally provides positive responses. From the results of this study it can be concluded that the Numbered Heads Together (NHT) type cooperative learning model is effectively applied in mathematics learning in class VII A MTsN 1 Kotabaru. Keywords: Implementation, Numbered Heads Together (NHT) type of cooperative learning.